Hubungan Tingkat Pengetahuan dan Pekerjaan Ibu dengan Pemberian ASI Ekslusif di Puskesmas Cipeunduey Kecamatan Malingping Kabupaten Lebak - Sulastri, Sulastri; Lestari, Euis Desi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Breast milk (ASI) is important for the most appropriate and good growth and development of babies. Exclusive breastfeeding is giving drinks or other food to babies aged zero to six months. The percentage of breast milk payments made in the Cipeunduey Community Health Center work area only reached 49.3% based on payroll statistics. This achievement is far below the national target, namely around 80%.The aim of this research is to determine the relationship between the performance of Exclusive ASI employees and the level of knowledge and understanding in the workplace at the Cipeundeuy Community Health Center, Malingping sub-district, Lebak Regency in 2024. This research is analytical and uses a cross-sectional research design. In this table, the population is parents who have children aged 0 to 12 months or a total of 12,217 people. A total of 95 people were surveyed using a purposive sampling technique. The validity and reliability of the research instruments used in this study have been evaluated. Data were analyzed using the Chi Square test. Results show that there is a relationship between the mother's level of knowledge and exclusive breastfeeding investment with a 2-sided Asymptotic Significance value of 0.002, and there is a relationship between the mother's work performance and exclusive breastfeeding investment with a 2-sided Asymptotic value. The significance value is 0.032. The results of this study show that there is a relationship between the level of education and employment of parents and the purchase of exclusive breast milk. Keywords: Knowledge, Work, Exclusive Breastfeeding  ABSTRAK Air Susu Ibu (ASI) penting untuk tumbuh kembang bayi yang paling tepat dan baik. Pemberian ASI eksklusif adalah memberikan minuman atau makanan lain untuk bayi yang umurnya nol hingga enam bulan. Persentase pembayaran ASI yang dilakukan di wilayah kerja Puskesmas Cipeunduey hanya mencapai 49,3% berdasarkan statistik payroll. Pencapaian ini jauh di bawah target nasional yaitu sekitar 80%.          Untuk mengetahui hubungan kinerja pegawai ASI Eksklusif dengan tingkat pengetahuan dan pemahaman di tempat kerja Puskesmas Cipeundeuy kecamatan Malingping Kabupaten Lebak pada tahun 2024. Penelitian ini bersifat analitik dan menggunakan desain penelitian cross-sectional. Pada tabel tersebut, populasinya adalah orang tua yang memiliki anak usia 0 sampai 12 bulan atau berjumlah 12.217 orang. Total ada 95 orang yang disurvei dengan teknik purposive sample. Validitas dan reliabilitas instrumen penelitian yang digunakan dalam penelitian ini telah dievaluasi. Data dianalisis menggunakan uji Chi Square. Menunjukkan terdapat hubungan antara tingkat pengetahuan ibu dengan investasi ASI eksklusif dengan nilai Asymptotic Significance 2 sisi sebesar 0,002, dan terdapat hubungan antara prestasi kerja ibu dengan investasi ASI eksklusif dengan nilai Asymptotic 2 sisi. Nilai signifikansi sebesar 0,032.adanya hubungan antara tingkat pendidikan dan pekerjaan orang tua dengan pembelian ASI eksklusif. Kata Kunci: Pengetahuan, Pekerjaan, ASI Eksklusif